2020
DOI: 10.3390/ijerph17197133
|View full text |Cite
|
Sign up to set email alerts
|

Association between Lifestyle Behaviors and Health-Related Quality of Life in a Sample of Brazilian Adolescents

Abstract: This study aimed to analyze the association between lifestyle behaviors and health-related quality of life (HRQoL) among Brazilian adolescents. We evaluated 739 adolescents (51.0% girls; mean age, 16.4 ± 1.0 years) from the mesoregion Grande Florianópolis, Brazil. Participants were asked to complete an online questionnaire and sex, age, mother’s education, health-related quality of life, physical activity, screen time indicators, sleep duration, diet, cigarette smoking, alcohol drinking, and drug experimentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…No consistent findings were reported across exposure categories. However, consistent findings in some studies were observed as null for homework [ 117 ], and sedentary time [ 71 ]. More homework was favourable for social-emotional indicators [ 118 ] and unfavourable for social-emotional indicators [ 119 ].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…No consistent findings were reported across exposure categories. However, consistent findings in some studies were observed as null for homework [ 117 ], and sedentary time [ 71 ]. More homework was favourable for social-emotional indicators [ 118 ] and unfavourable for social-emotional indicators [ 119 ].…”
Section: Resultssupporting
confidence: 59%
“…For the cross-sectional studies, findings were consistently reported as null in 2/12 studies [ 71 , 117 ], while more sedentary behaviour was favourable in 1/12 studies [ 118 ], unfavourable in 1/12 studies [ 119 ], and mixed findings were reported for 8/12 studies [ 39 , 63 , 65 , 68 , 120 123 ]. No consistent findings were reported across exposure categories.…”
Section: Resultsmentioning
confidence: 99%
“…Another important aspect to consider is that HRQoL varies with age 3,4 and the socioeconomic, cultural and environmental conditions of the adolescents 5 . To date, studies that have analyzed the relation between different types of sedentary behavior (television, computer, videogame and cellphone time) and HRQoL in adolescents are scarce, especially in middle-high income countries such as Brazil 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al 18 in a study carried out in the southern region of Brazil, analyzed the association between screen time measured by five activities (studying, working, watching videos, videogames and using social media/chat applications) and HRQoL. Adolescents whose screen time at work was above four hours / day showed a reduction in HRQoL (β = -2.38; 95%CI: -4.52; -0.25).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al, for example, conducted a systematic review of cross-sectional and longitudinal studies on the subject and found evidence that a higher level of physical activity and less time spent in sedentary behavior are associated with higher HRQoL among the general population of children and adolescents [ 13 ]. Other studies point to the following as negative indicators of HRQoL in adolescence: lack of sleep, excessive workload, drug use [ 14 ], high levels of screen time [ 15 ], use of social networks [ 16 ], excess weight [ 17 ] and use of psychoactive substances [ 18 ]. However, in addition to habits or lifestyles, there are social and psychological factors that contribute to young people’s well-being and therefore influence their HRQoL.…”
Section: Introductionmentioning
confidence: 99%